ANALISIS JUAL BELI BUAH KELAPA SAWIT MENURUT PERSPEKTIF IMAM SYAFI’I DI DESA TANJUNG PARING KECAMATAN DANAU SELULUK KABUPATEN SERUYAN PROVINSI KALIMANTAN TENGAH - Lilit Biati; Ribut Suprapto; Mamlukhah; Aji Jufriyanto (Jurnal Ekonomi Syariah Darussalam, 2023)
This study describe to determine whether the practice of buying and selling oil palm fruit in Tanjung Paring Village, Danau Seluluk District, Seruyan Regency, Central Kalimantan Province, is in accordance with the law of buying and selling according to Imam Syafi'I. Research with a qualitative approach and data analysis techniques using interviews. The results show the suitability of the practice of buying and selling oil palm fruit according to the perspective of Imam Syafi'i, which from the harvesting process to the selling process is in accordance with what has become its main goal. Ripe palm fruit is then harvested and taken out into the street to be weighed, then the buyer or weigher will come to the place for the weighing process, when the weighing process the seller and the buyer witness firsthand how the weighing process and the results or wages are received directly by the seller after the weighing process is complete.